2020
DOI: 10.21608/jcvr.2020.90231
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic of Cefquinome After Single I.V Administration Alone and Concurrent with Meloxicam in Goats

Abstract: The active profile of cefquinome in goats was concentrated after single intravenous organization of cefquinome alone and single intravenous organizations in goats pretreated with meloxicam at a portion of 2 mg/kg b.wt. Serum groupings of cefquinome were dictated by utilizing superior fluid chromatography (HPLC). Following compartmental examination, a two-compartment open model best portrayed the fixation time information of cefquinome after i.v. organization The outcomes uncovered that after a solitary intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The simulation was modified by considering the metabolism as a chemical reaction to predict the drug diffusion in this situation. In the studies performed by Baert and De Backer, [ 28 ] Salamah et al, [ 29 ] and Roosan and Sharma, [ 30 ] the half‐life of MLX was reported to be about 20 h.…”
Section: Simulation Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation was modified by considering the metabolism as a chemical reaction to predict the drug diffusion in this situation. In the studies performed by Baert and De Backer, [ 28 ] Salamah et al, [ 29 ] and Roosan and Sharma, [ 30 ] the half‐life of MLX was reported to be about 20 h.…”
Section: Simulation Studymentioning
confidence: 99%
“…The simulation was modified by considering the metabolism as a chemical reaction to predict the drug diffusion in this situation. In the studies performed by Baert and De Backer, [28] Salamah et al, [29] and Roosan and Sharma, [30] the half-life of MLX was reported to be about 20 h. Pseudo-ternary phase diagrams of oil-surfactant-water systems were obtained based on the experimental data. The ME area in the phase diagrams should be large enough to achieve an adequate formulation, therefore the diagrams with a large area of the ME zone were labelled as acceptable, and those with an inadequate ME area were labelled as not acceptable.…”
Section: Prediction Of the Effect Of Metabolism On Drug Diffusionmentioning
confidence: 99%
See 1 more Smart Citation